Implementation of performance-based forced/displacement hybrid seismic design applied to a steel-framed building (Gaceta Técnica, 2024)
The Hybrid Force-Displacement (HFD) Method combines the advantages of both seismic designs, applying the performance-based design approach, starting with a deformation design, using input variables in it, where the values of maximum mezzanine drifts and maximum roof displacements that exceed the elastic limit of the sections, are controlled, using three performance levels .Each of these levels is represented by an elastic spectrum of accelerations and another elastic spectrum of displacements, to carry out the seismic design by forces, where the procedure involves modifying the spectrum, scaling its ordinates and thus obtaining a representation of the three levels of performance. In this way, the maximum ceiling responses are obtained for each performance level and with these the respective reduction or behavior factors are calculated. To illustrate the application of the Method, a 7-story building was studied, structured in moment-resistant steel frames, located in an area of high seismic demand, such as Valparaíso, Chile. The procedure is validated by applying nonlinear dynamic time history analysis using records of strong earthquakes that occurred in the subduction zone
Keywords: Hybrid Force-Displacement Method; HFD method; moment frame buildings; maximum roof displacement; mezzanine drifts